2020
DOI: 10.3390/biomedicines8100380
|View full text |Cite
|
Sign up to set email alerts
|

Lupeol, a Plant-Derived Triterpenoid, Protects Mice Brains against Aβ-Induced Oxidative Stress and Neurodegeneration

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that represents 60–70% of all dementia cases. AD is characterized by the formation and accumulation of amyloid-beta (Aβ) plaques, neurofibrillary tangles, and neuronal cell loss. Further accumulation of Aβ in the brain induces oxidative stress, neuroinflammation, and synaptic and memory dysfunction. In this study, we investigated the antioxidant and neuroprotective effects of the natural flavonoid lupeol in the Aβ1–42 mouse model of AD. An In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…The western blot analysis was assessed as previously described with minor changes [ 25 , 26 , 27 ]. In brief, an equal volume of 20–30 μg of proteins (extracted from the ipsilateral cortex) was mixed with 2× Sample Buffer (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The western blot analysis was assessed as previously described with minor changes [ 25 , 26 , 27 ]. In brief, an equal volume of 20–30 μg of proteins (extracted from the ipsilateral cortex) was mixed with 2× Sample Buffer (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, BACE exerts β-secretase activity in the brain, promoting AD pathology [ 44 ]. Neurodegeneration induced by ICV injection of Aβ 1-42 in mice significantly increased BACE expression [ 49 ]. In addition, BACE cleaves APP and subsequently generates sAPPβ and C99 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental procedures were conducted in accordance with the Animal Ethics Committee (IACUC) of the Division of Applied Life Science, Department of Biology, Gyeongsang National University, Korea (Approval ID: 125). We used male mice in this study because they are resistant to stress, tough ecological conditions, and hormonal alteration [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…with Aβ 1–42 (Aβ 1–42 group), and (3) mice injected with Aβ 1–42 and NAM (via I.P route) NAM + Aβ 1–42 (250 mg/kg for 1 week); dosages of NAM were selected following previously published studies [ 17 ]. The NAM-alone group was not examined in the current study, as no ill effects of NAM have previously been reported in the brain [ 17 , 23 ]. Fresh NAM was prepared on daily basis in a normal saline solution followed by the needed volume of injection, and it was injected into the mice for treatment.…”
Section: Methodsmentioning
confidence: 99%